Exogenous gibberellin improves the yield and quality of basil (Ocimum basilicum L.) and chervil (Anthriscus cerefolium L.) plants grown under salinity stress conditions - El haddaji, Hamza; Akoudad, Mustapha; Skalli, Ali; Moumen, Abdelmajid; Bellahcen, Said; Maach, Mostapha; rahhou, Abderrahmane; Baghour, Mourad (Plant Science Today, 2024)
Gibberellins play a crucial role as plant hormones in the regulation of various aspects of plant growth and development. They are involved in processes such as seed germination, breaking plant and bud dormancy, and counteracting the effects of auxin. Additionally, gibberellins promote leaf expansion, stimulate stem elongation, and contribute to flower development and fruit set. The objective of this study was to investigate the effects of gibberellic acid (GA3) treatments (T0: 0 ppm, T1: 1 ppm, and T2: 10 ppm) on the growth regulation and physiological parameters of basil and chervil plants under salinity stress conditions (150 mM NaCl). The study explored various growth outcomes and biochemical parameters, including chlorophyll, proteins, soluble sugars, proline, and nitrate. The results indicate that the application of gibberellic acid alleviated the adverse effects of high salinity and resulted in enhanced biomass production. In comparison to the control treatment, foliar surface values for basil and chervil increased by 15% and 35%, respectively, in T2. Moreover, root lengths of basil and chervil reached their highest values in T2, showing a 16% increase for basil and a 33% increase for chervil. Carotenoid levels were positively influenced by GA3 treatments, reaching high concentrations in T2, exceeding T0 levels by 41% for basil and 83% for chervil. Additionally, under T2 treatment, protein and glucose levels increased by factors of 2.7 and 1.7, respectively, in basil plants and by factors of 2.1 and 1.7, respectively, in chervil plants. The application of gibberellic acid led to a 33% reduction in proline content for basil and a 27% reduction for chervil compared to the T0 treatment.